2015
DOI: 10.1039/c5dt00080g
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine/guanosine-3′,5′-bis-phosphates as biocompatible and selective Zn2+-ion chelators. Characterization and comparison with adenosine/guanosine-5′-di-phosphate

Abstract: Although involved in various physiological functions, nucleoside bis-phosphate analogues and their metal-ion complexes have been scarcely studied. Hence, here, we explored the solution conformation of 2′-deoxyadenosine- and 2′-deoxyguanosine-3′,5′-bisphosphates, 3 and 4, d(pNp), as well as their Zn(2+)/Mg(2+) binding sites and binding-modes (i.e. inner- vs. outer-sphere coordination), acidity constants, stability constants of their Zn(2+)/Mg(2+) complexes, and their species distribution. Analogues 3 and 4, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 52 publications
(81 reference statements)
2
10
0
Order By: Relevance
“…The process is presumably initiated by coordination of the diphosphates to the Zn atom, in line with previous experimental evidence [17,19,31]. Moreover, it is conceivable that the Zn ion is coordinated by the phosphate groups of ADP and ethanol molecules, since in water a stability constant of 5 × 10 4 is reported [32].…”
Section: Zn-sal Ethanol Solution Saturated With Adpsupporting
confidence: 85%
“…The process is presumably initiated by coordination of the diphosphates to the Zn atom, in line with previous experimental evidence [17,19,31]. Moreover, it is conceivable that the Zn ion is coordinated by the phosphate groups of ADP and ethanol molecules, since in water a stability constant of 5 × 10 4 is reported [32].…”
Section: Zn-sal Ethanol Solution Saturated With Adpsupporting
confidence: 85%
“…These Δδ values may imply on inner-and outer-sphere coordination for 11-Zn(II) and 7-Zn(II) complexes, respectively. 26 Unlike Zn(II) binding to 7, 9 and 11, no shift of the signals was observed upon Mg(II)-titration (Fig. S8-S13, ESI †), indicating a clear preference of MDPT-CE analogues to Zn(II).…”
Section: Characterization Of Representative Compounds 7 9 and 11 As Z...mentioning
confidence: 95%
“…54 Yet, recently we found that 2′-dG3′5′PO, 3, coordinates to Zn(II) via both phosphate moieties through bridging water molecules. 47 Hence, a 4O coordination sphere of 3 is more likely.…”
Section: Research Strategymentioning
confidence: 99%
“…Zn(II) complexes of analogues 1 (log K M ML 4.65), and 3 (log K M ML 4.75), are 100-fold more stable than those of the corresponding complexes with Mg(II) ions. 47 Currently, there is an urgent need for biocompatible metalion chelators capable of antioxidant activity and disassembly of Aβ-aggregates as potential therapeutics for AD. The promising antioxidant activity of analogues 1-6, 46 and their demonstrated affinity to Zn(II) ions 47 and Fe(II) ions, 46 encouraged us to evaluate them as agents for the dissolution of Aβ 42 -Zn(II)/ Cu(II) aggregates targeting the identification of novel biocom- Organic & Biomolecular Chemistry Paper patible, water soluble AD therapeutics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation